Thermal efficiency of a flat-plate solar collector filled with Pentaethylene Glycol-Treated Graphene Nanoplatelets: An experimental analysis. (October 2019) - Alawi, Omer A.; Mohamed Kamar, Haslinda; Mallah, A.R.; Kazi, S.N.; Sidik, Nor Azwadi Che
Highlights: Thermophysical properties of covalently functionalized Pentaethylene Glycol-Treated Graphene Nanoplatelets were measured. Thermal efficiency of PEG-GNPs nanofluids were experimentally discussed. Different mass flow rates, inlet temperatures and heat flux intensities were considered as main parameters. A MATLAB code was developed to estimate the statistical coefficients. Abstract: The effects of using aqueous nanofluids with the presence of Pentaethylene Glycol-Treated Graphene Nanoplatelets as the working fluids on the thermal performance of flat-plate solar collectors (FPSCs) were investigated experimentally. Water-based nanofluids were prepared with the concentrations of 0.025, 0.05, 0.075, and 0.1 wt%. Then the thermophysical properties were measured. Experimental setup and a MATLAB program were used to study the thermal performance of FPSCs-based nanofluids. The fluid inlet temperatures used in this study were 303, 313, and 323 K, and the flow rates were 0.00833, 0.01667, and 0.025 kg/s. Meanwhile, 500, 750 and 1000 W/m 2 were set for the heat flux intensities. As the weight concentration was increased, thermal conductivity, dynamic viscosity, and density also improved, while specific heat decreased. The efficiency of FPSC increased as the flow rate and heat flux intensity were increased. However, the efficiency of FPSC decreased when the temperature of the fluid inlet was increased. Compared to water, the FPSC efficiency recorded an increase of up to 10.7%, 11.1%, and 13.3% for PEG-GNP nanofluids at different mass flow rates. Finally, the regression model was developed through MATLAB to predict the thermal efficiency coefficients of FPSC.